Analisis Pengelolaan Lingkungan Kegiatan Penambangan Bahan Galian Tanah Uruk - Aussie Amalia; Hammam Fawwaz (Prosiding ESEC, 2023)
The need for building materials, especially piled up soil, is increasing along with the increase in the construction of facilities and infrastructure. Under these conditions, mining activities for the extraction of piled up soil minerals are also increasing. These mining activities will certainly have an impact on the surrounding area from an economic, environmental and social perspective. Therefore, this research aims to find solutions for mining activities that have an impact on the surrounding area by managing, restoring and improving the quality of the environment and ecosystem so that they can function again according to their designation. This research method uses a descriptive approach by providing a detailed description of how the environmental management plan for the land after mining activities. In addition, this research is also aimed at projecting land conditions when mining activities take place with land conditions when environmental management has been carried out. The projected condition of the land will be processed using ArcGis and Global Mapper software. The post-mining environmental management plan is carried out based on the identification of potential mining impacts. Post-mining environmental management will be carried out using revegetation techniques and land arrangement according to the procedures for post-mining environmental management stages. Environmental management will be carried out every year in order to minimize environmental damage and stabilize green areas. This environmental management activity will restore the function of the mining land to its original state (before mining), namely to become rice fields and moor areas.